One More Way How to Improve the Higher Education Teaching - Dobrovska, Dana (e-Pedagogium, 2018)
Much of higher education stresses the elimination of emotions in exchange for cool, analytic detachment. The idealized picture of the impartial student who engages in logically precise reasoning is the traditional norm to which we wish our students to aspire. Students confronted with the average university teaching are often left baffled why anyone would devote his or her life to the study of such limp material. But the traditional lecture format is not always the most effective way of transferring information. That is why we should pay attention to the powerful affective impact that a live lecture can deliver.There is no doubt students like to attend some teachers' classes more than the other's. Social psychology and sociology researched the topic of charismatic leaders trying to analyse their personal profiles and methods.In our paper we intend to shed more light on the concept of teacher charisma and to identify qualities charismatic teaching is characterized by.
Keywords: teaching; learning; teacher behaviour; charisma; charismatic teaching